Genomic and transcriptomic resources for candidate gene discovery in the Ranunculids (2021)
Premise Multiple transitions from insect to wind pollination are associated with polyploidy and unisexual flowers in Thalictrum (Ranunculaceae), yet the underlying genetics remains unknown. We generated a draft genome of Thalictrum thalictroides, a representative of a clade with ancestral floral traits (diploid, hermaphrodite, and insect pollinated) and a model for functional studies. Floral transcriptomes of T. thalictroides and of wind‐pollinated, andromonoecious T. hernandezii are presented as a resource to facilitate candidate gene discovery in flowers with different sexual and pollination systems. Methods A draft genome of T. thalictroides and two floral transcriptomes of T. thalictroides and T. hernandezii were obtained from HiSeq 2000 Illumina sequencing and de novo assembly. Results The T. thalictroides de novo draft genome assembly consisted of 44,860 contigs (N50 = 12,761 bp, 243 Mbp total length) and contained 84.5% conserved embryophyte single‐copy genes. Floral transcriptomes contained representatives of most eukaryotic core genes, and most of their genes formed orthogroups. Discussion To validate the utility of these resources, potential candidate genes were identified for the different floral morphologies using stepwise data set comparisons. Single‐copy gene analysis and simple sequence repeat markers were also generated as a resource for population‐level and phylogenetic studies. Keywords: draft genome, floral transcriptome, pollination syndrome, Ranunculaceae, sexual system, Thalictrum hernandezii, Thalictrum thalictroides